2000
DOI: 10.1038/sj.onc.1204027
|View full text |Cite
|
Sign up to set email alerts
|

The Crk signaling pathway contributes to the bombesin-induced activation of the small GTPase Rap1 in Swiss 3T3 cells

Abstract: Rap1 is a small GTPase implicated in cell proliferation and di erentiation. The mechanisms how endogenous Rap1 is activated by many mitogenic stimuli including the neuropeptide bombesin remained unclear. Here we analyse which signaling pathways are necessary for Rap1 activation. Bombesin-mediated Rap1 activation in Swiss 3T3 and primary mouse embryo ®broblasts requires signaling components similar to those being essential for complex formation between p130Cas and Crk adapter proteins. The Crk/CRKL-binding regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…As previously mentioned, apoptin is a cytoplasmic molecule but nuclear localization occurs upon phosphorylation at Thr108 in transformed cells, thus in CML-cells it is predominantly nuclear. These interactions and trans-activation of CrkL and c-Crk II by activated Bcr-Abl kinase and their functional consequences are well documented [35], [62]. In the current study, we demonstrated for the first time that apoptin inhibits phosphorylation of CrkL in Bcr-Abl expressing cells.…”
Section: Discussionsupporting
confidence: 71%
“…As previously mentioned, apoptin is a cytoplasmic molecule but nuclear localization occurs upon phosphorylation at Thr108 in transformed cells, thus in CML-cells it is predominantly nuclear. These interactions and trans-activation of CrkL and c-Crk II by activated Bcr-Abl kinase and their functional consequences are well documented [35], [62]. In the current study, we demonstrated for the first time that apoptin inhibits phosphorylation of CrkL in Bcr-Abl expressing cells.…”
Section: Discussionsupporting
confidence: 71%
“…Coexpression of CrkII and Ga12 acted synergistically in the activation of Rho and SRF, and an SH3 mutant of CrkII was able to inhibit the Ga12-mediated SRF activation. Consistent with our idea, it has been reported that Crk forms a complex with its binding partners in response to stimuli mediated by heterotrimeric G-proteins, including LPA stimulation, which acts predominantly through the G12 family (Casamassima and Rozengurt, 1997;Posern et al, 2000). Taken together, we conclude that CrkII is involved in the regulation of Rho and SRF by Ga12.…”
Section: Roles Of Crkii In the Signal Pathway Leading To Rho And Srf supporting
confidence: 77%
“…However, inducible Crk/CRKL complex formation and activation of Rap1 has been observed in di erent cell types and with several di erent stimuli (Ichiba et al, 1997;Garcia-Guzman et al, 1999;Alsayed et al, 2000;Du et al, 2000;Posern et al, 2000;Sakkab et al, 2000Sakkab et al, , 2001Xing et al, 2000). In some of these cases, for example in HGF-stimulated human embryonic kidney epithelial cells and Swiss 3T3 mouse ®broblasts stimulated with bombesin, it was clearly shown that Rap1 activation is dependent on Crk family adaptors Sakkab et al, 2000Sakkab et al, , 2001.…”
Section: C3gmentioning
confidence: 99%
“…According to a plethora of reports using various cell lines, p130Cas and its siblings play in concert with Crk family adaptors and di erent enzymes a major role in the reorganization of the cytoskeleton during cell shape changes and cell migration (Klemke et al, 1998;Cheresh et al, 1999;and others) and in mediating signal transmission from integrins (Nojima et al, 1995). Signals from soluble growth factors like bombesin also require Crk ± Cas complexes (Rozengurt, 1998;Posern et al, 2000, and references therein; see also Table 1 for other factors). Within the year 2000, reports from one group have indicated that the human p130Cas homologue, which they renamed BCAR1, plays a role in the antiestrogen resistance of breast cancer cells (Brinkman et al, 2000;van der Flier et al, 2000a,b).…”
Section: Sh3mentioning
confidence: 99%